2007
DOI: 10.1172/jci32426
|View full text |Cite
|
Sign up to set email alerts
|

Immune suppression or enhancement by CD137 T cell costimulation during acute viral infection is time dependent

Abstract: CD137 is expressed on activated T cells and ligands to this costimulatory molecule have clinical potential for amplifying CD8 T cell immunity to tumors and viruses, while suppressing CD4 autoimmune T cell responses.To understand the basis for this dichotomy in T cell function, CD4 and CD8 antiviral immunity was measured in lymphocytic choriomeningitis virus (LCMV) Armstrong-or A/PR8/34 influenza-infected mice injected with anti-CD137 mAbs. We found that the timing of administration of anti-CD137 mAbs profoundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…During murine CMV infection, 4-1BB suppresses CD8 T cell responses against acute epitopes, but enhances CD8 T cell responses during the latent phase (43). Supporting this study, agonistic anti-4-1BB Abs improve or impair T cell responses against acute infection with LCMV and influenza depending on the time of application (44). Similar to CD27, 4-1BB required Fasdriven apoptosis to induce contraction of CD8 T cell responses (44).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…During murine CMV infection, 4-1BB suppresses CD8 T cell responses against acute epitopes, but enhances CD8 T cell responses during the latent phase (43). Supporting this study, agonistic anti-4-1BB Abs improve or impair T cell responses against acute infection with LCMV and influenza depending on the time of application (44). Similar to CD27, 4-1BB required Fasdriven apoptosis to induce contraction of CD8 T cell responses (44).…”
Section: Discussionmentioning
confidence: 67%
“…Supporting this study, agonistic anti-4-1BB Abs improve or impair T cell responses against acute infection with LCMV and influenza depending on the time of application (44). Similar to CD27, 4-1BB required Fasdriven apoptosis to induce contraction of CD8 T cell responses (44). The costimulatory pathway through CD28 has not been reported to downregulate T cell responses by itself but is counteracted by the inhibitory family member CTLA4 that also binds B7 molecules (45).…”
Section: Discussionmentioning
confidence: 84%
“…Anti-4-1BB Abs can enhance CD8 T cell responses to viruses (20,21,57), and a single dose of anti-4-1BB Ab can completely correct the CD8 memory defect in 4-1BBL-deficient mice in a nonlethal influenza model (20). However, attempts to correct the defect in response to severe influenza in 4-1BBL-deficient mice by systemic administration of anti-4-1BB agonistic Abs were unsuccessful, and resulted in accelerated disease (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al [38] have reported studies in lymphocytic choriomeningitis virus-infected mice, which show that, depending on the timing of treatment, anti-4-1BB mAb can either cause activation-induced cell death or enhance anti-viral immunity. When given early post-infection, anti-4-1BB was immunosuppressive, with depletion of virus-specific CD81 T cells.…”
Section: Discussionmentioning
confidence: 99%